Multiple livelihoods and social relations in the South African Lowveld, 1986-2013 - van der Waal, Kees (C. S.) (Review of African political economy, 2017)
Despite improvements in the last two decades, rural communal areas in South Africa remain dumping grounds, requiring multiple livelihood strategies and social adaptations. Local experience of dispossession forms the backdrop to individual and collective responses to changes in the role of land, labour and reproduction. The ethnographic research focused on a rural settlement in the former Gazankulu Bantustan in the period 1986-2013. Shifts in the mix of livelihoods were related to changing gender and generational relationships. Individual livelihood strategies aimed at diversifying sources of income and collective actions were directed at getting rid of criminals and accessing state resources.